Considerations in the study of trophies : the effect of skull cutting on the real value of roe buck trophies = Razmatranja u trofejistici : učinak reza lubanje na stvarnu vrijednost trofeja srnjaka - Krapinec, Krešimir (Array, 2019)
Roe deer is Laurasiatherian mammal from the family of Cervidae. It is autochthonous and one of the most valued trophy game species in Croatia (Zorić 2014.). Antlers (left and right branch) with complete or part of the skull are regarded as trophy. Despite the fact that roe deer antlers are easily accessible trophies, formulas for their evaluations are still largely debated. It is a consequence of large number of elements that need to be evaluated, possible use of coefficient instead of measuring volume and mass, and potential differences in trophy preparation. Guidelines of the International Council for Game and Wildlife Conservation (CIC) instructs that skulls should be cut through the eye cavities leaving intact nasal bones on the trophy. If otherwise cut or left intact with maxillar teeth, deduction of 65 or 90g is foreseen. Considering the fact that weight and density of bones varies between populations, we hypothesize that above mentioned deductions do not represent real values. Therefore the aim of this research was to determine the deviations from actual mass. A total of 40 roe buck skulls originating from the area of Central Croatia were analysed. All skulls were weighed 3 times, initially when intact, after shallow cut and after proscribed cut. Obtained data were statistically analysed. Following the shallow cut, skull is lighter for 25 to 52 g, which is 11 g less than proscribed 65 g. In other words application of shallow cut will result in the loss in trophy value. In cases of intact skulls loss in weight is related to gross skull mass. In this case even 68 to 70% of variability are explained by gross skull mass (R2=0.680; p<0.0001 – linear function, or R2=0.699; p<0.01 – potency function). According to the intersection of the lines (obligate deduction of 90 g and dependence of mass loss due to the cutting) milestone in the mass is at 310 g gross.